Về một phương pháp kết hợp ngôn ngữ dữ liệu với ngôn ngữ lập trình - Tâng, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2016)
A programming language and the data base language will be combined one to another in such a way, that an application source program, which a mixture of statements on host and data base languages  instead, can be now separabed into two source modules, the one on the host language and the other on the data base. By the host standard compiled into object modules. The LINKEP EDITOR of the operating system links those modules into a load module that corresponds to the original mixed program.